Perceived Sources of Stress Among The Students Of a Medical College Of Southern Punjab - Jan, Hassan; Dogar, Fahd Mehtab Ud Din; Khan, Hafiz Ahmed Zeb; Abideen, Malik Zain Ul; Shaukat, Malik Saleem; Malik, Aeeza (Journal of Rawalpindi Medical College, 2024)
Objective: To assess the frequency of perceived sources of stress among undergraduate dental students. Methodology: The cross-sectional study was carried out at a superior college, Multan. Sample size 125 was calculated with 80% power of test and 5% level of significance with 91% high level of stress. The collection of data was based on two components: a list of 14 items, a perceived stress scale, and demographic information and academics. Data was entered and analyzed in SPS V25.0. Results: A total of 125 students were included. The mean age was 21.25 ± 1.25. There were 61(48.8%) male and 64(51.2%) female. The response rate in this study was 83% (125/150). The mean PSS score was 30.88+13.2 with a median of 29.0 (IQR 22-39). The Mean PSS score for female students was 31.3+9.49 while the male students 30.3+16.34. The mean PSS score of less than 80% of the last exam marks for students was 32.9+10.9 and >80% of exam marks were 27.8+15.6. Only year of study, last exam marks for students and siblings were significant (p < 0.05) with PSS score; and the females reported significant levels of perceived stress than their male counterparts. Frequency of examinations, performance in practicals, disappointment with the lectures in class, lengthy academic curriculum, worries about the future & periodic examinations performance were rated as severe Conclusion: The conclusion of the study, was that students reported higher levels of stress. Demographic factors play an essential role in medical student’s stress. PSS stress scale was highly associated with demographic factors like Age, gender low exam marks and siblings can cause high stress levels among students. Keywords: Perceived stress, Students, Sources of stress, Score.